Maxillary Incisors of the Horse before and at the Beginning of the Teeth Shedding: Radiographic and CT Study - Francisco Miró; Carla Manso; Andrés Diz; Manuel Novales (Animals, 2020)
To gain insight into the radiographic appearance of maxillary deciduous incisors and dental germs of maxillary permanent incisors in the period prior to teeth shedding, radiographs and computed tomography (CT) of 25 horse skulls, with an estimated age of between 12 and 42 months, were studied. Data regarding morphology and development were obtained. Dental germs of first maxillary permanent incisors were identified radiographically as rounded radiolucent areas at the level of the apical parts of the first deciduous incisors, in skulls with an estimated age of twelve months. The first sign of crown mineralization of these dental germs appeared in skulls supposedly a few months older. Before teeth shedding, the unerupted, mineralized crowns of the first permanent incisor could be identified radiographically relatively caudal to the corresponding first deciduous incisors. The results of the present study indicate that radiographic intraoral images are suitable to identify the grade of development of the dental germs of maxillary permanent incisors. A detailed description of the radiographic appearance of deciduous incisors and dental germs of permanent incisors will help clinicians to expand their knowledge for diagnostic or treatment purposes.